FAKTOR DETERMINAN KEPUASAN DAN LOYALITAS KONSUMEN: PERAN PERSEPSI HARGA SEBAGAI PEMODERASI - Wowiling, Yessi Kristi; Wahyudi, Triyono Arief (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The purpose of the study was to analyze determinant factors, location and perceptions of service quality on tenant loyalty with tenant satisfaction and price perceptions as moderating variables. There were 75 respondents who participated in this study. This study uses multiple linear regression methods to analyze existing variables. The results of the study show that building location and perceived quality of services have a direct effect on tenant satisfaction; Tenant satisfaction has a direct effect on tenant loyalty; and Price perception has an indirect effect (moderation) between tenant satisfaction and tenant loyalty. Keywords: location, perceived service quality, tenant’s satisfaction, perceived price, tenant loyalty